İlköğretim okulu müdürlerinin liderlik yeterlik standartlarına ilişkin eğitimcilerin görüşleri - Güngör, Hasan Ferhat (My University, 2001)
The purpose of this research was to determine to what extent various groups from education circles in Turkey accept the "performance" standards that are a component of the standards in six leadership competency areas with substandards in knowledge, dispositions and performances components. The standards have been devised and set for school leaders to be used as a criterion for the training, recruitment, induction and assessment of school principals. In accordance with this purpose, a survey was developed by the researcher out of the "performances" component of the "Standards for School Leaders." The survey, then, was conducted to the working-universe of the research, a total sample group of 2290 subjects consisting of five subgroups; 184 university faculty members, 95 chief province school officers, 155 primary school supervisors, 464 primary school principals and deputy principals, and 1392 primary school teachers. The ratio of the valid questionnaires to the working universe comes out to be %84,9. The data obtained were processed through SPSS 9.0 Statistical Software and Microsoft Excel 2000. For each competency area of leadership standards; distribution frequencies and percentages of the sample groups were computed. Competency areas of leadership were, then, subjected to one-way variance analysis versus profession to find out whether any significant differences are observed. The findings of the research could be mentioned as follows:. Considering the means for each standard item, it can be stated that the performance standards for school leaders have highly been accepted by all sample subgroups with an overall mean of 4,53.. Sorting the means by sample groups indicated that the highest level of acceptance was shown by chief province school officers and school principals whereas the lowest by supervisors. IV. The results of Tukey(HSD) test displayed some significant differences among sample subgroups in the performance standards in each of the six competency areas of leadership. o In the areas of both visionary leadership and educational leadership, there is a significant difference between primary school principals, teachers and supervisors. Supervisors' acceptance level of the performance standards in this area is relatively and significantly lower than that of principals' and teachers'. o The significant difference in both organizational leadership and ethical leadership is between supervisors and principals. Yet again, supervisors are below the mark in terms of the level of acceptance. o Concerning community leadership, the significant difference is between school principals, faculty staff and supervisors. Not surprisingly supervisors are on the lower side again. o In political leadership, difference is between chief province school officers and faculty staff, teachers. Faculty staff and teachers stand on the lower side in accepting the standards in this area.. Three of the first five standard items accepted the most comes out to be from the area of ethical leaderhip. All items accepted the most include similar key phrases such as "being fair," "justice," "trust," "respect" and "kindness". The findings of this research could be used in improving the pre-service and in-service training programs through including courses on leadership competencies and applied courses that should enable principals turn knowledge into dispositions and performances. The data could also be of great use in redefining the roles of principals which would reorientate everything related to principalship by devising a set of leadership standards for school leaders.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2001
Keywords: İlköğretim okulu müdürleri; Eğitim liderliği; Türkiye’de yapılan araştırmalar